2019
DOI: 10.1149/2.0161910jes
|View full text |Cite
|
Sign up to set email alerts
|

Varying Power Generation in Ultra Low-Frequency Mechanical Energy Harvesting of Piezoelectrochemical Materials

Abstract: Piezoelectrochemical (PEC) materials convert mechanical energy into electrochemical energy through Faradaic charge transfer, allowing energy harvesting at very low frequencies. Electric power is generated through micro-Hz cyclical compression of commercially available lithium-ion batteries with varying PEC effects. Difference in power generation between different PEC systems is analyzed based on standard charge/discharge curve and the relationship between the coupling of mechanical stress and voltage. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The concept of hydrogel ionic diode, with further optimization in material selection and architecture design, holds promise as a new form of efficient energy harvesting at ultralow frequencies, and can be also applied to other ion‐based energy devices including fuel cells and batteries. [ 41,42 ] It is anticipated that hydrogel ionotronics will enable novel ionic‐current‐based flexible and wearable devices for sensing, soft robotics, machine‐human interface, and energy harvesting. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…The concept of hydrogel ionic diode, with further optimization in material selection and architecture design, holds promise as a new form of efficient energy harvesting at ultralow frequencies, and can be also applied to other ion‐based energy devices including fuel cells and batteries. [ 41,42 ] It is anticipated that hydrogel ionotronics will enable novel ionic‐current‐based flexible and wearable devices for sensing, soft robotics, machine‐human interface, and energy harvesting. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, only a few materials that harvest energy in this fashion have been evaluated in recent literature. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Experimental demonstrations of this effect have been reported in lithium-cobalt-oxide-graphite, 5,7,8 sodium-phosphorus, 6 lithium-carbon, 9 lithiumsilicon, 10,11 and lithium-aluminum systems, 12 among others. Our group has previously demonstrated that commercially available lithium-ion pouch cells exhibit this effect and can be used in an energy-harvesting cycle by mechanically loading and unloading the cells.…”
Section: Introductionmentioning
confidence: 96%
“…A recently identified mechanical micro-energy-harvesting mechanism, called the piezoelectrochemical (PEC) effect, is used in one such harvester. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] PEC systems, also known as mechano-electrochemical systems or strain energy harvesters, among other names, have higher theoretical energy densities and much lower harvesting frequencies than other mechanical energy harvesters. 5 This makes them ideal for harvesting applications that require higher energy densities and lower frequencies than piezoelectrics can provide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations